Social Norms and Female Labor Force Participation in Bangladesh: The Role of Social Expectations and Reference Networks - Luna Bellani; Kumar Biswas; Sebastian Fehrler; Paul Marx; Shwetlena Sabarwal; Syed Rashed Al-Zayed Josh (Institute of Labor Economics (IZA), 2023)
About 50% of Bangladesh's female youth working-age population is not in employment, education, or training (NEET). Reducing this number is an important policy goal. However, there is a broad consensus that pervasive gender norms hamper this goal in Bangladesh and other countries from the Global South. In this study, we analyze the social basis of support for young working women. It departs from a theoretical understanding of norms as conditional upon expectations in one's reference network. Based on vignette experiments, we show that manipulating expectations about acceptance of female employment by others influences personal support for women taking up work. Moreover, we address the question of whose views matter. Manipulating the expectation that fathers (or husbands in the case of married NEETs) support the employment of their daughters (wives) has a particularly strong effect on respondents' support. In contrast, the stance of religious authorities and peers has surprisingly little relevance. Our evidence suggests that (expectations about) traditional views of fathers and husbands regarding the role of females are a key obstacle to a higher labor force participation of young women in Bangladesh.
Keywords: D91; J22; J16; Z10; 330; Bangladesh; female labor force participation; gender norms; social expectations; survey experiments